Tryptophan-specific peptide modification through metal-free photoinduced N-H alkylation employing N-aryl glycines - Yin, Jianhui; Huang, Wenjing; Guo, Changyong; Liu, Chao; Gao, Fei; Hu, Honggang (Chinese chemical letters, 2024)
Tryptophan (Trp) carries a unique heteroaromatic indole side chain and plays a critical role in peptide or protein modification. Herein, we have reported a metal-free photoinduced N-H alkylation strategy using N-aryl glycines for specific modification of tryptophan-containing peptides. The robustness of our approach is demonstrated by its wide substrate scope, excellent isolated yields, as well as almost unobservable side effects. Using this highly efficiently metal-free condition, alkylated Trp-containing peptides can be smoothly assembled. This study provides a reliable and practical tool for the chemo-selective modification of various tryptophan containing oligopeptides. Various alkylated Trp-containing peptides were synthesized by metal-free photoinduced decarboxylative alkylation in acceptable to excellent yields. [Display omitted]